2020
DOI: 10.3390/molecules25163723
|View full text |Cite
|
Sign up to set email alerts
|

Virtual Screening of FDA-Approved Drugs against LasR of Pseudomonas aeruginosa for Antibiofilm Potential

Abstract: Pseudomonas aeruginosa is a Gram-negative pathogenic bacterium that is present commonly in soil and water and is responsible for causing septic shock, pneumonia, urinary tract and gastrointestinal infections, etc. The multi-drug resistance (MDR) phenomenon has increased dramatically in past years and is now considered a major threat globally, so there is an urgent need to develop new strategies to overcome drug resistance by P. aeruginosa. In P. aeruginosa, a major factor of drug resistance is associated to th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
17
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 35 publications
(18 citation statements)
references
References 51 publications
1
17
0
Order By: Relevance
“…Stability of these ligands were further mediated through π-mediated interactions with Tyr66 or Trp90, in addition to hydrophobic contacts with Ala41, Tyr52, Val78, Leu82, Ile125, and Met127. Similar polar interactions were illustrated by Sadiq et al where several FDAapproved sulphonamide antibacterial agents and their carboxamide-based close analogues showed favored hydrogen bonding with QscR homologous residues; Trp62 and Asp75 as well as additional polar contacts with Tyr58 and Ser129 through docking and subsequent molecular dynamics simulations [54]. Significant π-π hydrophobic interaction with Tyr66 was also depicted stable for all sulphonamide antibacterial agents across the simulation studies.…”
Section: Discussionsupporting
confidence: 78%
See 1 more Smart Citation
“…Stability of these ligands were further mediated through π-mediated interactions with Tyr66 or Trp90, in addition to hydrophobic contacts with Ala41, Tyr52, Val78, Leu82, Ile125, and Met127. Similar polar interactions were illustrated by Sadiq et al where several FDAapproved sulphonamide antibacterial agents and their carboxamide-based close analogues showed favored hydrogen bonding with QscR homologous residues; Trp62 and Asp75 as well as additional polar contacts with Tyr58 and Ser129 through docking and subsequent molecular dynamics simulations [54]. Significant π-π hydrophobic interaction with Tyr66 was also depicted stable for all sulphonamide antibacterial agents across the simulation studies.…”
Section: Discussionsupporting
confidence: 78%
“…Moreover, residues around 80-90, 135-140, 150-165, 180-195, and 210-225 ranges were of the most flexible pattern (∆RMSF down to the highest negative values~−5.00 Å). Unlike the previously described QS proteins, the simulated CviR proteins depicted an extra stabilized residue region (45)(46)(47)(48)(49)(50)(51)(52)(53)(54)(55) near the N-terminus showing a significant immobility profile (∆RMSF~1.20 Å). Compounds 2, 11, 13, and 17 depicted high negative ∆RMSF values across the flexible regions; 180-195 and 210-225 residue range.…”
Section: Analysis Of Ligand-cvir C Violaceum Complexesmentioning
confidence: 91%
“…He also reported that the QS-related mRNA gene expressions were down-regulated by cladodionen. A recent study by Sadiq et al [245] reported sulfamerazine, a synthetic FDA-approved compound as an inhibitor of LasR by performing virtual screening and molecular docking by employing a pharmacophore hypothesis based screening and elucidating the stability of their binding conformation by a simulation study. A study by Baldelli et al [246] suggested two antibiotic compounds, namely, nitrofurazone and erythromycin estolate as PqsE inhibitors by screening a library of FDA-approved drugs and found that these compounds reduce the expression of PqsE-dependent virulence and formation of biofilm in P. aeruginosa PAO1 model strain.…”
Section: In Silico Approach To Control P Aeruginosa Biofilmsmentioning
confidence: 99%
“…PPIs have been continuously studied for presenting other activities, in addition to those already known and used commercially, and the most reported in the literature are the anti-infective ones. These properties are reported against different infectious agents: antibacterial activity, against Pseudomonas aeruginosa (Sadiq et al 2020), Mycobacterium tuberculosis (Mdanda et al 2017), Ureaplasma urealyticum (Nagata et al 1995), Enterococcus faecalis (Jonkers et al 1996), and Staphylococcus aureus (Jonkers et al 1996;Vidaillac et al 2007); antifungal, against Candida albicans (Biswas et al 2001;Monk et al 1995), Candida spp. (Siavoshi et al 2012), and Saccharomyces cerevisiae (Monk et al 1995 (Riel et al 2002;Skinner-Adams et al 1997), Schistosoma mansoni (Almeida et al 2015;Ellakany et al 2019), Giardia lamblia (Hernández-Ochoa et al 2017), and Tritrichomonas foetus (Sutak et al 2004;Kather et al 2007); antiviral, against SARS-CoV-2 (COVID-19) (Aguila and Cua 2020;Homolak and Kodvani 2020) and rhinovirus (Sasaki et al 2005).…”
Section: Commentarymentioning
confidence: 99%